Development of Augmented Reality Traditional Musical Education Applications - Zulkifli Syahrir Ramadhan; Reza Andrea; Suswanto (Politeknik Pertanian Negeri Samarinda, 2022)
Technology that is developing very rapidly today is no exception in the world of education, the convenience offered by technology cannot be denied by shifting the way children learn who were born and raised in the digital era. In the field of education, augmented reality technology has been widely implemented, such as applications that use augmented reality book aids. This study aims to create an alternative application as a learning medium for the introduction of traditional musical instruments with a multimedia development method by an elementary school educational institution. In this study, the augmented reality method used is Image Based Tracking, which uses images as markers. The tool that helps in making AR is the Vuforia SDK which is used as a storage area marker. By doing this research, the results were obtained in the form of an Augmented Reality Traditional Musical Instrument Recognition application that runs on the Android platform and respondent testing using the User Acceptance Testing (UAT) method with a value of 86%.